6 Effect of fresh lily and rhubarb powder on chronic stress depression in rats. (19th December 2016) - Li, Yan; Wang, Tan; Xi, Peng; Miao, Mingsan
Abstract : Objectives: To examine the effect of fresh lily and rhubarb powder on chronic stress depression on rats. Methods: A chronic unpredictable mild stress rat model of depression was established. Body mass, sugar consumption and open-field behavior were measured to assess the effect of fresh lily and rhubarb powder on rat behavior. Plasma MDA levels and erythrocyte SOD activity were measured using a kit, the fluorescence of brain tissue homogenates was measured to determine the 5-HT, NE and DA content of amine neurotransmitters, and the thymus and spleen were also examined for any changes. Results: In the rat chronic stress depression model, rats administered large and small doses of fresh lily and rhubarb powder over 3 weeks significantly increased their body weight ( p < 0.05), while rats administered large, medium and small doses of fresh lily and rhubarb powder significantly increased their consumption of sucrose ( p < 0.05). There was also a trend towards reduced plasma levels of MDA ( p < 0.01) and the 3 min vertical motion score was significantly increased ( p < 0.05). Large doses of fresh lily and rhubarb powder significantly increased erythrocyte SOD activity ( p < 0.05), while small doses of fresh lily and rhubarb powder significantly increased rat brain NE, 5-HT and DA levels ( p < 0.01) and significantly increased the rat 3 min horizontal motion score ( p < 0.05). Conclusions: Fresh lily and rhubarb powder exhibited a therapeutic effect on rats with depression.